Porous polyether sulfone / layered double hydroxide nanosheet composite anion exchange membrane as well as preparation method and application thereof

Through the method of growing the oligoral LDH nano -nanoplastment on the PES porous base, the problem of rapid loss of alkaline metal in the alkaline doped pCam exchange membrane has been solved, and the efficient alkali doped and long -term stable operation have been achieved, which improves hydrogen. Performance and life of fuel cells.

CN119361773AActive Publication Date: 2025-01-24XI AN JIAOTONG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411494597.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The rapid loss of alkali metals in alkali-doped anion exchange membranes leads to a degradation of membrane electrode performance and short test life, making it impossible to achieve long-term stable operation.

Method used

Using the preparation method of porous polyethersulfone/layered double hydroxide nanosheets composite anion exchange membrane, the oligolayer LDH nanosheets are grown in situ on the PES porous substrate to provide more adsorbable sites and slow down the adsorption of alkali metals. drain.

Benefits of technology

The alkali doping amount is significantly increased, the service life of the membrane electrode is extended, and the stability and recycling performance of the hydrogen fuel cell are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361773A_ABST
    Figure CN119361773A_ABST
Patent Text Reader

Abstract

The invention discloses a porous polyether sulfone / layered double hydroxide nanosheet composite anion exchange membrane as well as a preparation method and application thereof. The method comprises the following steps: preparing AlOOH from an aluminum isopropoxide solution and nitric acid; the preparation method comprises the following steps: adding AlOOH into deionized water to obtain an AlOOH solution, adding nitric acid into the AlOOH solution, and stirring and refluxing to obtain AlOOH sol; the preparation method comprises the following steps: coating a PES porous substrate with AlOOH sol, and putting the PES porous substrate coated with the AlOOH sol into a mixed solution of magnesium salt and hexamethylenetetramine for sealing treatment to obtain the porous polyether sulfone / layered double hydroxide nanosheet composite membrane. Through in-situ growth of the few-layer LDH nanosheets, the tensile property and the alkali doping amount of the PES porous substrate-few-layer LDH nanosheet composite film are improved, and meanwhile, the loss of alkali metal is greatly slowed down through high affinity of the few-layer LDH nanosheets to alkali and partial filling of pores of the porous substrate; therefore, the fuel cell performance of the PES porous substrate-few-layer LDH nanosheet composite membrane is improved, and the service life of the PES porous substrate-few-layer LDH nanosheet composite membrane is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field, and in particular relates to a porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane and a preparation method thereof. Background Art

[0002] The energy crisis and environmental problems caused by the excessive use of fossil fuels have become major issues facing the world. Therefore, the development and utilization of new clean energy has become the focus of attention of countries around the world. Hydrogen energy is one of the most competitive representatives of new clean energy due to its high calorific value and pollution-free characteristics. Hydrogen fuel cells, as efficient application devices of hydrogen energy, have attracted widespread attention from researchers around the world. Among them, proton exchange membrane fuel cells are an important type of hydrogen fuel cells. After decades of research and development, proton exchange membrane fuel cells have become mature, but they still face the following problems: (1) high cost in the preparation process of proton exchange membranes, (2) limited reserves and high prices of precious metal catalysts, (3) high-purity hydrogen must be used to avoid efficiency reduction caused by catalyst poisoning, and (4) high corrosion in acidic working environments requires the use of corrosion-resistant components. The faster electrode redox reaction kinetics and low corrosion in alkaline working environments of anion exchange membrane fuel cells allow the use of non-precious metal catalysts, expand the selectivity of accessory materials, and are expected to reduce the cost of catalyst materials and hydrogen use, thereby greatly reducing the cost of fuel cells.

[0003] As the core component of fuel cells, anion exchange membranes with high ion conductivity, stability, reliability and low price have always been the goal pursued by researchers. However, due to the higher molecular weight and lower mobility of OH-, the conductivity of anion exchange membranes is often lower than that of proton exchange membranes. There are two main ways to improve the ion conductivity of anion exchange membranes in the prior art. One is the modification of cationic functional groups, such as quaternary ammonium groups, imidazolium groups, guanidine groups, etc.; the other is to use stable organic polymer materials to dope alkali metal solutions to achieve high ion conductivity through doping with alkali metal solutions, such as polybenzimidazole membranes doped with KOH.

[0004] At present, cationic functional group modification is the mainstream method for preparing anion exchange membranes, but cationic functional group modified anion exchange membranes often have the following disadvantages: complex modification and poisoning steps, which make the cationic functional groups have unstable performance and insufficient durability. Due to the existence of these problems, there are still no mature commercial products for fuel cell anion exchange membranes. For alkali-doped anion exchange membranes, although they do not require a complex cationic functional group modification process and have good structural stability, this method is unsustainable because it completely relies on the alkali metal doped in the membrane. The generation of water during the electrode reaction will cause the alkali metal in the membrane electrode to lose rapidly, and long-term stable operation cannot be achieved. At present, the performance degradation caused by the loss of alkali metals is a common problem of alkali-doped anion exchange membranes. How to solve the problem of alkali loss has become the key to the development of alkali-doped anion exchange membranes. Summary of the invention

[0005] The present invention provides a porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane and a preparation method and application thereof, so as to solve the problems of poor performance and short test life of alkali-doped anion exchange membrane caused by the loss of alkali metal.

[0006] The present invention provides a method for preparing a porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane, comprising: adding nitric acid to the aluminum isopropoxide solution to obtain a first solution, wherein the first solution maintains a preset pH value, and evaporating the solvent of the first solution to obtain AlOOH; Adding AlOOH to deionized water to obtain an AlOOH solution, adding nitric acid to the AlOOH solution to obtain a second solution, and stirring and refluxing the second solution to obtain an AlOOH sol; The AlOOH sol is coated on the PES filter fiber to obtain a PES porous substrate coated with the AlOOH sol; The PES porous substrate coated with AlOOH sol is placed in a mixed solution of magnesium salt and hexamethylenetetramine for sealing treatment, and then heated to obtain a porous polyethersulfone / layered double hydroxide nanosheet composite membrane after the sealing treatment.

[0007] The preset pH value of the first solution is between 3 and 4.

[0008] The concentration of the nitric acid is 0.5-2 M.

[0009] The pH of the second solution is less than 4.

[0010] The magnesium salt is one of magnesium nitrate hexahydrate and magnesium chloride, and the molar ratio of the magnesium salt to hexamethylenetetramine in the mixed solution of the magnesium salt and hexamethylenetetramine is 1:1-1:1.5.

[0011] The molar concentration of the AlOOH sol is 0.5-1.5 mol L -1 .

[0012] The AlOOH sol is coated on the PES filter fiber to obtain a PES porous substrate coated with the AlOOH sol, specifically: The AlOOH sol was ultrasonically treated for 30 to 60 minutes, and the AlOOH sol was uniformly coated on the PES filter fiber by soaking and vacuum filtration to obtain a PES porous substrate coated with the AlOOH sol.

[0013] The heating condition after the sealing treatment is heating at 80-90° C. for 20-24 hours.

[0014] The present invention also provides a porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane prepared by the above preparation method.

[0015] The present invention also provides the use of the porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane in a hydrogen fuel cell.

[0016] Compared with the prior art, the present invention has at least the following beneficial effects: The preparation method provided by the present invention can realize the in-situ growth of few-layer LDH nanosheets in a PES porous substrate, while ensuring the unoriented growth state of the few-layer LDH nanosheets, which is conducive to overcoming the anisotropy of two-dimensional nanosheets. Through the in-situ growth of the few-layer LDH nanosheets, the PES porous substrate is protected, so that the swelling rate of the PES porous substrate-few-layer LDH nanosheet composite membrane is reduced, and its tensile strength is improved. The in-situ growth of the few-layer LDH nanosheets greatly improves the specific surface area of ​​the PES porous substrate-LDH nanosheets, provides more adsorbable sites for the adsorption of alkali, and greatly improves the alkali doping amount. At the same time, the high affinity of the few-layer LDH nanosheets to the alkali and the partial filling of the pores of the porous substrate greatly slow down the loss of alkali metals, thereby improving the fuel cell performance and service life of the PES porous substrate-few-layer LDH nanosheet composite membrane. The preparation method provided by the present invention is simple and does not involve complicated chemical reaction processes. The in-situ growth process of LDH nanosheets is simple and does not involve complicated chemical reaction processes. It also does not involve cationic functional group modification and does not require the participation of poisoning agents.

[0017] The PES porous substrate-few-layer LDH nanosheet composite membrane provided by the present invention is used in a hydrogen fuel cell, which improves the stability of the hydrogen fuel cell, and the operating temperature can be up to 110°C, and the -2 During the constant current discharge process, the voltage decay rate of 100 h is only about 16%, and its performance can be restored by secondary alkali doping, which shows good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings to be used in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 This is a flow chart of the method for preparing the porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane of the present invention; Figure 2 is the X-ray diffraction pattern of AlOOH synthesized during the preparation process; Figure 3 This is an electron microscope surface image of the existing PES porous substrate; Figure 4 It is an electron microscope cross-sectional view of the existing PES porous substrate; Figure 5 This is the electron microscope surface image of the PES porous substrate-few-layer LDH nanosheet composite membrane prepared in Example 1.

[0020] Figure 6 This is an electron microscope cross-sectional view of the PES porous substrate-few-layer LDH nanosheet composite membrane prepared in Example 1; Figure 7 This is an electron microscope magnified image of the few-layer LDH nanosheets on the PES porous substrate-few-layer LDH nanosheet composite membrane prepared in Example 1; Figure 8 (1) is the surface image and EDS element analysis of the PES porous substrate-few-layer LDH nanosheet composite membrane; (2) is the cross-sectional image and EDS element analysis of the PES porous substrate-few-layer LDH nanosheet; Fig. 9 (1) is the Nyquist curve and fitting curve of the AC impedance of the PES porous substrate after doping with alkali at different temperatures; (2) is the Nyquist curve and fitting curve of the AC impedance of the PES porous substrate-few-layer LDH nanosheet composite membrane after doping with alkali at different temperatures; Fig.10 The conductivity of PES porous substrate and PES porous substrate-few-layer LDH nanosheet composite membrane at different temperatures; Fig.11(1) is a test chart for the power density of the PES porous substrate membrane fuel cell; (2) is a test chart for the durability of the PES porous substrate membrane; (3) is a test chart for the power density of the PES porous substrate-few-layer LDH nanosheet composite membrane fuel cell prepared in Example 1; (4) is a test chart for the durability of the PES porous substrate-few-layer LDH nanosheet composite membrane prepared in Example 1. DETAILED DESCRIPTION

[0021] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.

[0023] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0024] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.

[0025] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.

[0026] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" represents that all real numbers between "6-22" are listed in this document, and "6-22" is just an abbreviation of these numerical combinations.

[0027] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.

[0028] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0029] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.

[0030] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.

[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0032] See also Figure 1 The present invention provides a method for preparing a porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane, comprising the preparation of boehmite (AlOOH) sol; coating the boehmite sol on a PES porous substrate; and in-situ growth of a few-layer LDH nanosheet, specifically: adding nitric acid to the aluminum isopropoxide solution to obtain a first solution, wherein the pH value of the first solution is maintained between 3 and 4, and after cooling to room temperature, treating the first solution by evaporating the solvent to obtain AlOOH; Add AlOOH to deionized water, stir at 80-90°C for 1 hour to completely dissolve AlOOH to obtain an AlOOH solution, add nitric acid to the AlOOH solution to obtain a second solution, the pH of the second solution is less than 4, stir and reflux the second solution for 6-8 hours to obtain an AlOOH sol; The AlOOH sol was ultrasonically treated for 30-60 min, and the AlOOH sol was uniformly coated on the filter fibers of the PES porous substrate by soaking and vacuum filtration to obtain a PES porous substrate coated with the AlOOH sol. The PES porous substrate coated with AlOOH sol is placed in a mixed solution of magnesium nitrate hexahydrate and hexamethylenetetramine, and after sealing treatment, it is heated at 80-90°C for 20-24h to obtain a porous polyethersulfone (PES) / layered double hydroxide (LDH) nanosheet composite anion exchange membrane (PES porous substrate-few-layer LDH nanosheet composite membrane).

[0033] In some embodiments, the concentration of nitric acid is 0.5-2 M. In the process of preparing the first solution, the role of nitric acid is to provide an acidic environment to induce the hydrolysis of aluminum isopropoxide. In the process of preparing the second solution, it is to obtain a stable AlOOH sol, because the sol system obtained when the pH of the solution is less than 4 is the most stable. The main role of nitric acid is to adjust the pH of the solution to 4 or below. Nitric acid of different concentrations can be selected according to the requirements for the final solution concentration.

[0034] In some embodiments, magnesium salts such as magnesium nitrate hexahydrate, magnesium chloride, etc. are used as magnesium sources, and hexamethylenetetramine or urea, which are hydrolyzed into alkaline substances at high temperatures, are used to provide the alkaline environment required for the reaction. The selected substance in this case is magnesium nitrate hexahydrate and hexamethylenetetramine. The molar ratio of magnesium salt to hexamethylenetetramine in the mixed solution of magnesium salt and hexamethylenetetramine is between 1:1 and 1:1.5.

[0035] In some embodiments, the molar concentration of the AlOOH sol is 0.5-1.5 mol L -1 The specific concentration can be selected according to the pore size of the selected porous substrate. High-concentration AlOOH sol may cause pore blockage of the porous substrate during immersion and filtration, and the process of AlOOH coating the PES substrate cannot be completed. Therefore, the concentration of the configuration should be selected according to the pore size of the porous substrate.

[0036] This method can realize the in-situ growth of few-layer LDH nanosheets in a porous substrate, while ensuring the non-directional growth state of the nanosheets, which is conducive to overcoming the anisotropy of two-dimensional nanosheets. The preparation process of this method is simple, and no toxic reagents are involved; it does not involve a complex chemical reaction process, and no toxic reagents are involved; the prepared PES porous substrate-few-layer LDH nanosheet composite membrane has a large operating temperature range and good durability and recyclability. Through the in-situ growth of few-layer LDH nanosheets, the original porous substrate is protected, so that the swelling rate of the PES porous substrate-few-layer LDH nanosheet composite membrane is reduced, and its tensile strength is improved. In previous tests of alkali-doped anion exchange membranes, such as polybenzimidazole-doped KOH type anion exchange membranes, the alkali doping amount is low, and during the test process, the generation and flow of water molecules will cause the rapid loss of KOH, thereby greatly reducing the power density and test life of the fuel cell. The porous substrate provides a larger space for KOH doping, and the in-situ growth of few-layer LDH nanosheets greatly increases the specific surface area of ​​PES porous substrate-LDH nanosheets, providing more adsorption sites for KOH adsorption, which greatly increases the doping amount of KOH. At the same time, the high affinity of few-layer LDH nanosheets for KOH and the partial filling of the pores of the porous substrate greatly slow down the loss of KOH, thereby improving the fuel cell performance and service life of the PES porous substrate-few-layer LDH nanosheet composite membrane.

[0037] In the following examples, unless otherwise specified, all materials used can be obtained through common channels; and the test methods adopted are conventional methods in the art.

[0038] Example 1 Dissolve 11.3 g of aluminum isopropoxide in 100 ml of deionized water and stir at 85° C. for 20 min to ensure that the aluminum isopropoxide is completely dissolved to obtain an aluminum isopropoxide solution; The aluminum isopropoxide solution was continuously stirred for 2 h, and 1 M HNO3 was slowly added dropwise to the aluminum isopropoxide solution during the stirring process to keep the pH of the aluminum isopropoxide solution between 3 and 4. After cooling to room temperature, the aluminum isopropoxide solution was treated by evaporating the solvent to obtain AlOOH; Weigh 6 g of AlOOH and dissolve it in 100 mL of deionized water. Stir at 85 °C for 1 h to completely dissolve AlOOH to obtain AlOOH solution. Then slowly drop HNO3 (1 M, 9.5 mL) into the AlOOH solution and stir and reflux for 6 h to obtain AlOOH sol. The molar concentration is 1 mol L -1 The AlOOH sol was treated with ultrasound for 30 min to avoid possible particle agglomeration; the AlOOH sol was uniformly coated on the PES filter fiber by combining soaking and vacuum filtration. The PES porous substrate coated with AlOOH sol was placed in 80 ml of a mixed solution prepared with 2.56 g of magnesium nitrate hexahydrate (purity > 99%) and 1.82 g of hexamethylenetetramine (purity > 99%) for sealing treatment. The molar ratio of magnesium nitrate hexahydrate to hexamethylenetetramine was 1:1.3. After sealing treatment, the substrate was heated at 85°C for 24 hours to obtain a PES porous substrate-oligolayer LDH nanosheet composite membrane.

[0039] Example 2 Dissolve 11.3 g of aluminum isopropoxide in 100 ml of deionized water and stir at 85° C. for 20 min to ensure that the aluminum isopropoxide is completely dissolved to obtain an aluminum isopropoxide solution; The aluminum isopropoxide solution was continuously stirred for 2 h, and 0.5 M HNO3 was slowly added dropwise to the aluminum isopropoxide solution during the stirring process to keep the pH of the aluminum isopropoxide solution between 3 and 4. After cooling to room temperature, the aluminum isopropoxide solution was treated by evaporating the solvent to obtain AlOOH; Weigh 6 g of AlOOH and dissolve it in 100 mL of deionized water. Stir at 85 °C for 1 h to completely dissolve AlOOH to obtain AlOOH solution. Then slowly drop HNO3 (0.5 M, 19 mL) into the AlOOH solution and stir and reflux for 8 h to obtain AlOOH sol. The molar concentration is 1 mol L -1 The AlOOH sol was treated with ultrasound for 30 min to avoid possible particle agglomeration; the AlOOH sol was uniformly coated on the PES filter fiber by combining soaking and vacuum filtration. The PES porous substrate coated with AlOOH sol was placed in 80 ml of a mixed solution prepared with magnesium nitrate hexahydrate and hexamethylenetetramine for sealing treatment, wherein the molar ratio of magnesium nitrate hexahydrate to hexamethylenetetramine was 1:1.5. After the sealing treatment, the substrate was heated at 80°C for 24 hours to obtain a PES porous substrate-few-layer LDH nanosheet composite membrane.

[0040] Example 3 Dissolve 11.3 g of aluminum isopropoxide in 100 ml of deionized water and stir at 85° C. for 20 min to ensure that the aluminum isopropoxide is completely dissolved to obtain an aluminum isopropoxide solution; The aluminum isopropoxide solution was continuously stirred for 2 h, and 1 M HNO3 was slowly added dropwise to the aluminum isopropoxide solution during the stirring process to keep the pH of the aluminum isopropoxide solution between 3 and 4. After cooling to room temperature, the aluminum isopropoxide solution was treated by evaporating the solvent to obtain AlOOH; Weigh 6 g of AlOOH and dissolve it in 200 mL of deionized water. Stir at 90 °C for 1 h to completely dissolve AlOOH to obtain AlOOH solution. Then slowly drop HNO3 (1 M, 9.5 mL) into the AlOOH solution and stir and reflux for 7 h to obtain AlOOH sol. The molar concentration is 0.5 mol L -1 The AlOOH sol was treated with ultrasound for 60 min to avoid possible particle agglomeration. The AlOOH sol was evenly coated on the PES filter fiber by combining soaking and vacuum filtration. The PES porous substrate coated with AlOOH sol was placed in 80 ml of a mixed solution prepared with magnesium nitrate hexahydrate and hexamethylenetetramine for sealing treatment. The molar ratio of magnesium nitrate hexahydrate to hexamethylenetetramine was 1:1.4. After the sealing treatment, the substrate was heated at 85°C for 20 hours to obtain a PES porous substrate-few-layer LDH nanosheet composite membrane.

[0041] Example 4 Dissolve 11.3 g of aluminum isopropoxide in 100 ml of deionized water and stir at 85° C. for 20 min to ensure that the aluminum isopropoxide is completely dissolved to obtain an aluminum isopropoxide solution; The aluminum isopropoxide solution was continuously stirred for 2 h, and 2 M HNO3 was slowly added dropwise to the aluminum isopropoxide solution during the stirring process to keep the pH of the aluminum isopropoxide solution between 3 and 4. After cooling to room temperature, the aluminum isopropoxide solution was treated by evaporating the solvent to obtain AlOOH; Weigh 9 g of AlOOH and dissolve it in 100 mL of deionized water. Stir at 85 °C for 1 h to completely dissolve AlOOH to obtain AlOOH solution. Then slowly drop HNO3 (2M, 4.8 mL) into the AlOOH solution and stir and reflux for 7 h to obtain AlOOH sol. The molar concentration is 1.5 mol L -1 The AlOOH sol was treated with ultrasound for 60 min to avoid possible particle agglomeration; the AlOOH sol was uniformly coated on the PES filter fiber by combining immersion and vacuum filtration; The PES porous substrate coated with AlOOH sol was placed in 80 ml of a mixed solution prepared with magnesium chloride and hexamethylenetetramine for sealing treatment, the molar ratio of magnesium chloride to hexamethylenetetramine being 1:1.3. After sealing treatment, the substrate was heated at 90°C for 20 hours to obtain a PES porous substrate-few-layer LDH nanosheet composite membrane.

[0042] The application of the PES porous substrate-few-layer LDH nanosheet composite membrane in Example 1 in a hydrogen fuel cell is specifically as follows: The PES porous substrate-oligolayer LDH nanosheet composite membrane in Example 1 was immersed in a supersaturated alkaline solution at room temperature, in this case, a 25 M KOH solution, and immersed at 80-90° C. for 3 h; The PES porous substrate-few-layer LDH nanosheet composite membrane was taken out after soaking, and the membrane electrode was assembled using a gas diffusion electrode (Suzhou Shengernuo) and the fuel cell performance was tested. The fuel cell performance was tested at 40℃, 60℃, 80℃, and 110℃ respectively. At the operating temperature of 95℃, the -1 The fuel cell life was tested with a current density of 100 cc / min. -1 All tests were conducted without back pressure. After completing the 100 h durability test, the second and third durability tests were conducted by re-immersing in KOH. The test results showed that the PES porous substrate-few-layer LDH nanosheet composite membrane had good recyclability.

[0043] As shown in Table 1, the swelling rate, tensile strength, alkali doping amount, etc. of the existing PES porous substrate (from Cobetter) and the PES porous substrate-few-layer LDH nanosheet composite membrane prepared in Example 1 were tested; and the fuel cell power density and durability performance of the PES porous substrate and the PES-few-layer LDH nanosheet composite membrane were tested and compared using a fuel cell test equipment. The test results are shown in Tables 1 and Fig.11 shown.

[0044] Table 1 Performance comparison of PES porous substrate and PES-few-layer LDH nanosheet composite membrane

[0045] See also Figure 2-11 As shown, Figure 2 The X-ray diffraction peaks of AlOOH synthesized during the preparation process are consistent with the standard diffraction peaks of AlOOH, confirming the successful synthesis of AlOOH. Figure 3 This is a scanning electron microscope image of the surface of the PES porous substrate. The pore structure distribution on the surface of the PES porous substrate is approximately uniform, the pore sizes vary, the average pore diameter is 220 nm, and the surface is flat and smooth. Figure 4 This is a scanning electron microscope image of the cross section of the PES porous substrate, and its internal structure shows a continuous honeycomb distribution. Figure 5 This is a surface scanning electron microscope image of the PES porous substrate-few-layer LDH nanosheet composite membrane prepared in Example 1. After the in-situ growth of the few-layer LDH nanosheets, the pore structure of the PES porous substrate can no longer be observed, and its surface has been covered by the few-layer LDH nanosheets. Figure 6 This is a scanning electron microscope image of the cross-section of the PES porous substrate-few-layer LDH nanosheet composite membrane prepared in Example 1. After the growth of the few-layer LDH nanosheets, it can be clearly observed that the fibers inside the original PES porous substrate have been completely coated with the few-layer LDH nanosheets, and the overall shape is approximately regular honeycomb. Figure 7 This is an enlarged picture of the few-layer LDH nanosheets on the PES porous substrate-few-layer LDH nanosheet composite membrane prepared in Example 1. The thickness is between 10 and 15 nm as measured by electron scanning microscopy. Figure 8 (1) and (2) are the surface and cross-sectional EDS elemental analysis images of the PES porous substrate-oligolayer LDH nanosheet composite membrane prepared in Example 1, respectively, and the components of LDH were successfully detected.

[0046] See also Fig. 9 After alkali doping, the AC impedance Nyquist curves of the PES porous substrate and the PES porous substrate-few-layer LDH nanosheet composite membrane prepared in Example 1 were tested at different temperatures and fitted using Zview software. The working environment of the fuel cell was provided by a fuel cell workstation (Scribner 850), and the AC impedance Nyquist curves of the two were tested using an electrochemical workstation (CHI760E). During the test, the perturbation voltage was 5 mV and the test frequency was 10~10 6 Hz. After the test, the impedance of the two at different temperatures was obtained by data fitting, and the Fig.10The conductivity data shown. At the same temperature, the conductivity of the PES porous substrate-few-layer LDH nanosheet composite membrane prepared in Example 1 is better than the conductivity of the existing PES porous substrate. The calculation formula is σ=L / (R∙S), σ is the conductivity, L is the membrane thickness, R is the resistance value obtained by fitting, and S is the electrode contact area.

[0047] See also Fig.11 After alkali doping, the fuel cell performance of the PES porous substrate and the PES porous substrate-few-layer LDH nanosheet composite membrane prepared in Example 1 were tested at different temperatures. The maximum power density of the PES porous substrate at 40°C can be 209.04 mW cm -2 The maximum power density at 60°C is 389.16 mW cm -2 At 80 °C, the evaporation of water molecules was accelerated due to the increase in temperature, resulting in gas leakage in the pore structure of the PES porous substrate. Now, the performance dropped sharply, and the maximum power density was only 15.58 mW cm -2 The operating temperature range of the PES porous substrate-few-layer LDH nanosheet composite membrane is from room temperature to 110°C, and its maximum power density is 303.23 mW cm at 40°C. -2 The maximum power density at 60°C is 429.60 mWcm -2 The maximum power density at 80°C is 562.48 mW cm -2 The maximum power density at 110°C is 455.63 mW cm -2 . 0.1 A cm -2 The durability of PES porous substrate and PES porous substrate-oligolayer LDH nanosheet composite membrane was tested at a constant current density. Considering the performance decay of PES porous substrate when the temperature rises, its durability was tested at 60°C. The test results showed that the voltage decay of PES porous substrate exceeded 50% within 2.5 h. This was mainly due to the generation of a large number of water molecules during the electrode reaction, which led to the rapid loss of doped KOH through the pore structure. The PES porous substrate-oligolayer LDH nanosheet composite membrane had a high affinity for KOH and its blocking effect on the pores, which greatly slowed down the loss rate of KOH. The voltage decay rate of PES porous substrate-oligolayer LDH nanosheet composite membrane was only about 16% in 100 h, and its performance could be restored by secondary alkali doping, showing good recycling performance.

[0048] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane, characterized in that: include: adding nitric acid to the aluminum isopropoxide solution to obtain a first solution, wherein the first solution maintains a preset pH value, and evaporating the solvent of the first solution to obtain AlOOH; Adding AlOOH to deionized water to obtain an AlOOH solution, adding nitric acid to the AlOOH solution to obtain a second solution, and stirring and refluxing the second solution to obtain an AlOOH sol; The AlOOH sol is coated on the PES filter fiber to obtain a PES porous substrate coated with the AlOOH sol; The PES porous substrate coated with AlOOH sol is placed in a mixed solution of magnesium salt and hexamethylenetetramine for sealing treatment, and then heated to obtain a porous polyethersulfone / layered double hydroxide nanosheet composite membrane after the sealing treatment.

2. The method for preparing the porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane according to claim 1, characterized in that: The preset pH value of the first solution is between 3 and 4.

3. The method for preparing the porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane according to claim 1, characterized in that: The concentration of the nitric acid is 0.5-2 M.

4. The method for preparing the porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane according to claim 1, characterized in that: The pH of the second solution is less than 4.

5. The method for preparing the porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane according to claim 1, characterized in that: The magnesium salt is one of magnesium nitrate hexahydrate and magnesium chloride, and the molar ratio of the magnesium salt to hexamethylenetetramine in the mixed solution of the magnesium salt and hexamethylenetetramine is 1:1-1:1.

5.

6. The method for preparing the porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane according to claim 1, characterized in that: The molar concentration of the AlOOH sol is 0.5-1.5 mol L -1 .

7. The method for preparing a porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane according to claim 1, characterized in that: The AlOOH sol is coated on the PES filter fiber to obtain a PES porous substrate coated with the AlOOH sol, specifically: The AlOOH sol was ultrasonically treated for 30 to 60 minutes, and the AlOOH sol was uniformly coated on the PES filter fiber by soaking and vacuum filtration to obtain a PES porous substrate coated with the AlOOH sol.

8. The method for preparing a porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane according to claim 1, characterized in that: The heating condition after the sealing treatment is heating at 80-90° C. for 20-24 hours.

9. A porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the porous polyethersulfone / layered double hydroxide nanosheet composite anion exchange membrane according to claim 9 in a hydrogen fuel cell.

Citation Information

Patent Citations

  • CNTs@SiO2@Ni / Al-LDH shell structure three-dimensional nanometer material and preparation method thereof

    CN104843805A

  • Preparation method of sol solution containing two-dimensional nano container supported corrosion inhibitor

    CN109399629A

  • Method for preparing Fe-cage intercalated layered double hydroxide nanofiltration membrane

    CN110639366A

  • Hydrotalcite in-situ growth composite membrane, and preparation method and application thereof

    CN112928322A

  • Preparation method of layered bimetal hydroxide / quaternized phenolphthalein polyarylether sulfone hybrid membrane

    CN115634573A